Design and Appraisal of Rural Transport Infrastructure : Ensuring Basic Access for Rural Communities - Lebo, Jerry; Schelling, Dieter (Washington, DC: World Bank, 2013)
Isolation contributes to rural poverty. Without a minimum of reliable and efficient access to locations of basic social and economic activities, rural life stagnates and local development prospects remain limited. Providing and maintaining a minimum level of access, referred to in this paper as basic access, is therefore a necessary element of any rural development strategy. Overcoming isolation necessitates holistic strategies. Approaches include improved logistics to support trade and communication, the promotion of transport services and intermediaite means of transport, improved quality and location of services, and the sustaianable provision of cost-effective transport infrastrucutre. Among these, the cost-effective design and appraisal of rural transport infrastructure (RTI) is the topic of this paper. A basic access approach to the provision of RTI is presented which gives priority to the provision and maintenance of reliable, all-season access. Basic access interventions are defined as the least-cost investments which provide a minimum level of all-season passability. In a majority of cases, this means single-lane, spot-improved earth or gravel roads. In situations where motorized basic access is not affordable, improvement of the existing path network and the construction of footbridges may be the only alternative. resources are scarce. Therefore the basic access approach should only employ the most appropriate and cost-effective interventions.